2000
DOI: 10.1046/j.1365-313x.2000.00936.x
|View full text |Cite
|
Sign up to set email alerts
|

Interactions between hy1 and gun mutants of Arabidopsis, and their implications for plastid/nuclear signalling

Abstract: Lhcb and other nuclear genes for chloroplastic proteins are regulated by several signals. Among them, light and retrograde signals from the plastid itself appear to act through closely related mechanisms. To investigate this interaction, we analysed an Arabidopsis mutant, hy1, deficient in plastidic heme oxygenase. hy1 is defective in phytochrome chromophore biosynthesis, which has other indirect effects on tetrapyrrole metabolism. We generated double mutants between hy1-6.2, genetically a null mutation, and t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
85
0

Year Published

2001
2001
2018
2018

Publication Types

Select...
4
2
2

Relationship

2
6

Authors

Journals

citations
Cited by 89 publications
(87 citation statements)
references
References 32 publications
2
85
0
Order By: Relevance
“…Their degree of`genome uncoupling' (Lhcb expression in the absence of functional chloroplasts) was similar to that observed in single mutants. These results can be interpreted as a metabolic (rather than genetic) interaction between HY1 and the GUN gene products (Vinti et al 2000). Several of the GUN loci were identi®ed.…”
Section: Gun Mutants and The Reverse Signalling Pathwaymentioning
confidence: 87%
“…Their degree of`genome uncoupling' (Lhcb expression in the absence of functional chloroplasts) was similar to that observed in single mutants. These results can be interpreted as a metabolic (rather than genetic) interaction between HY1 and the GUN gene products (Vinti et al 2000). Several of the GUN loci were identi®ed.…”
Section: Gun Mutants and The Reverse Signalling Pathwaymentioning
confidence: 87%
“…We have found that gun2 and gun3 are alleles of hy1 and hy2, respectively, and that hy1-1 and hy2-1 (28) are gun mutants. hy1-6.2, a null allele (34), is also a gun mutant (48). HY1 and HY2 are required for the synthesis of phytochromobilin (P⌽B) from heme.…”
Section: Discussionmentioning
confidence: 99%
“…HY1 encodes a heme oxygenase that converts heme to biliverdin IX␣ (BV; refs. 35 and 36), and HY2 is thought to encode a P⌽B synthase that converts BV to 3(Z)-P⌽B (37 (48). Because gun2 is an allele of hy1, and because gun2 and gun3 affect chlorophyll accumulation like gun4 and gun5, it is likely that gun2-gun5 mutations affect the same plastid-to-nucleus signaling pathway by perturbing tetrapyrrole synthesis.…”
Section: Discussionmentioning
confidence: 99%
“…The hy1-6.2 mutant has also been described (Vinti et al, 2000). These mutants are available through the Nottingham Arabidopsis Stock Centre.…”
Section: Plant Materials and Growth Conditionsmentioning
confidence: 99%
“…Lhcb1, in particular, has been found to be under the control of a variety of signals, including hormones, sugar, and particularly the circadian clock (Millar and Kay, 1996) and a signal through which nuclear gene expression responds to the physiological status of the plastid (plastid retrograde signals, Oelmu¨ller et al, 1986, Surpin et al, 2002. At least one class of 'plastid signals' has now been identified as a tetrapyrrole intermediary metabolite produced by plastids (Vinti et al, 2000;La Rocca et al, 2001;Mochizuki et al, 2001), specifically Mg-Proto (Strand et al, 2003). Very close connections appear to exist between both light and circadian clock responses of Lhcb (Wang and Tobin, 1998;Ma´s et al, 2003), and between light and 'plastid-signal' responses (Argu¨ello-Astorga and Herrera-Estrella, 1998;Lo´pez-Juez et al, 1998).…”
Section: Introductionmentioning
confidence: 99%